The extract of "shoe flower" (Hibiscus rosea sinensis L) leaves inhibit the spermatogenesis of ddy strain mice (Medical Journal of Indonesia, 2008)
This study was conducted in order to develop male contraception from plants, namely the "shoe flower" (Hibiscus rosea sinensis L) leaves. The objective of this study was to find out whether the extract of "shoe flower" leaves could inhibit the process of spermatogenesis on ddy strain mice. This research was performed in 3 groups and each group consisted of 8 mice. The control group was given 1% carboxy methyl cellulose (CMC) in 0.5 ml aquabides. The treatment group I was given the extract of "shoe flower" leaves 700 mg/kg BW and 1% CMC in 0.5 ml aquabides, and the second treatment group was given the extract of "shoe flower" leaves, 800 mg/kgBW and 1% CMC in 0.5 ml aquabides. The treatment were given for 40 days in accordance with the spermatogenesis cycle. Then, the production of histological slides of the mice testis and the observation of the slides using light microscope with magnification of 100x and 400x were done. Further, counting of the spermatogenic cells was done. At last the pictures of seminiferous tubulus cross-section of the three groups which consisted of spermatogenic cells were taken through light microscope with magnification of 100x and 400x using Fuji camera and Fuji film, 200 ASA. The results showed significant differences between the control, treatment I, and treament II group. There were decreased numbers of spermatogonia, pachyten primary spermatocytes and spermatids in treatment groups (P<0.01). The result of this study showed that the extract of "shoe flower" (Hibiscus rosea sinensis L) leaves, inhibited the process of spermatogenesis of ddy strain mice. It is hoped that the result of this study can be developed into a male contraception. (Med J Indones 2008; 17: 157-62)